Effects of joint immobilization and hindlimb unloading on collagen fibers of soleus muscles in rats - Ishikura, Hideki; Aihara, Kazuki; Ono, Takeya; Sato, Yuta; Umei, Namiko; Oki, Sadaaki; Tsumiyama, Wakako; Matsumoto, Tomohiro; Tasaka, Atsushi (Journal of Physical Therapy Science, 2017)
[Purpose] The purpose of this study was to determine whether collagen fibers cause a difference in a contracture resulting from a combination of joint fixation and hindlimb unloading as compared to joint fixation only. [Subjects and Methods] The subjects of this study were 21 female Wistar rats divided into 4 groups as follows: Control Group (CON, n=7); Joint Fixation Group (JF, n=7), Hindlimb Unloading Group (HU, n=7), Joint Fixation Plus Hindlimb Unloading Group (JF+HU, n=7). This study was conducted for 1-week. Ankle joint range of motion and positive areas of collagen using fluorescent stain were analyzed. [Results] Ankle joint range of motion in JF + HU showed an increase compared to that of JF. Positive areas of Type I collagen in JF+HU showed an increase as compared with that of JF. [Conclusion] The results of this study suggested that the difference in a contracture caused by only joint immobilization and by a combination of joint immobilization and hindlimb unloading were significantly associated with Type I collagen.